Antibiotic Resistance among Enteric Fever Pathogens in a Tertiary Care Children Hospital of Bangladesh - Rahman, Md Mizanur; Bhuiyan, AKM Tajuddin (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Enteric fever, a public health problem endemic in Bangladesh involves multiple systems. Fluoroquinolones and third generation cephalosporins are first line drugs used in treatment, which has led to increased minimal inhibitory concentration (MIC) of ciprofloxacin causing therapeutic failure. In recent years using these drug some treatment failure found. Objectives: To study the antibiotic resistance among enteric fever pathogens in young children and to study the isolation rate of S. typhi and S. paratyphi among different age groups of children. Methods: A prospective study was done in Pediatric Infectious & Community Pediatrics Department of Dhaka shishu (Children) Hospital among admitted children age 1 to 15 years from January 2018 to January 2019. During this period 62 blood culture samples with growth of S.typhi & S.paratyphi were processed. The antibiotic susceptibility was done by modified Kirby disk diffusion. Results: During this 1 year from 72 admission days, 216 suspected enteric fever children admitted in Pediatric Infectious & Community Pediatric Department. Out of these 216 patients, isolation rate of enteric fever pathogens by blood cultures was 62 (28.7%). Majority of the isolates were S. typhi (75.8%) and S. paratyphi A were 24.2%. Among them 40(64.5%) isolates were from 5 to 15 years of age. Antibiotic resistance pattern was Ampicillin 37.1%, Chloramphenicol 30.64%, Co-trimoxazole 35.48%, Ceftriaxone (0%), Azithromycin (19.35%), resistance or reduced susceptibility to Ciprofloxacin was found in 77.41%, Nalidixic acid 100%, ten isolates (16.12%) were MDR. The most susceptible antibiotic was ceftriaxone while most resistant was nalidixic acid. Conclusion: The increasing numbers of enteric fever pathogens with decreasing susceptibility to ciprofloxacin and azithromycin is a concern. Increasing dependency to ceftriaxone and cefixime may cause resistance to these drugs near future. So, we can choose older drugs again in some cases. DS (Child) H J 2019; 35(1) : 55-58